If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(2n-3)=73-n)
We move all terms to the left:
-5(2n-3)-(73-n))=0
We add all the numbers together, and all the variables
-5(2n-3)-(-1n+73))=0
We multiply parentheses
-10n-(-1n+73))+15=0
| (x+2)(x-2)+5=5(x+1) | | 11=7u-10 | | N+5=15;n | | -3/2x+16/5x=0 | | c+30.c=7000 | | x+(x+1)+(x+2)=198 | | 6(V+9)=5v+32 | | F(x)=x²-2x-24 | | 8x-28=3x-3 | | 24=5p-11 | | x+30.x=7000 | | x=1.66-4x=-x/4 | | -6=g/30-8 | | 2d-19=325 | | 3(8-x)=51 | | 12m=3m | | X-2/x+1=2/3 | | -6=g/30+8 | | (8x+5)^2=196 | | 1/8=2/5xx | | 14/6=y-5/12 | | -5/4u-1=7/6u+3/4 | | (x-7)^2-(81)=0 | | -6(-4v+8)-3v=6(v-8)-3 | | 5k+3=43 | | 3+2m=-11 | | -4+2r=-14 | | 5(x-2)=42.5 | | -4/3b-11=25 | | 49x^2+1=10 | | -10=|8b|−6 | | 18−3u=−24 |